Mental toughness profiles and their relations with achievement goals and sport motivation in adolescent Australian footballers - Gucciardi, D. F. (Journal of Sports Sciences, 2010)
The aims of this study were to identify the mental toughness profiles of adolescent Australian footballers and to explore the relations between the mental toughness clusters and achievement goals and sport motivation. A total of 214 non-elite, male Australian footballers aged 16-18 years (mean = 16.8, s = 0.7) provided self-reports of mental toughness, achievement goals, and sport motivation. Cluster analysis supported the presence of two-groups in which players evidenced moderate and high levels of all four mental toughness subscales. Significant multivariate effects were observed for achievement goals and sport motivation with the high mental toughness group favouring both mastery- and performance-approach goals and self-determined as well as extrinsic motivational tendencies. The results suggest that adolescent Australian footballers' self-perceptions of mental toughness fall within two clusters involving high and moderate forms of all four components, and that these profiles show varying relations with achievement goals (particularly mastery-approach) and sport motivation.